Cognitive Models of Professional Communication Discourse on Teaching the Interpreters - Moshchanskaya Y. Y. (Образование и наука)
The paper is devoted to the discourse on professional institutional communication and its modeling for training the interpreters. The aim of the study is the analysis of the cognitive models of the above discourse relating to the present development stage of the cognitive linguistics. The author makes the conclusion emphasizing the paradigmatic and syntagmatic orientation of the selected cognitive models and outlines the constant and variable factors for developing the didactic model of the professional communication discourse. The paper presents the discourse-analysis model of professional communication based on the systematic approach and designed for the case study of the mediated communication. The obtained results can be used for training both the interpreters and other professionals for whom the discursive competence is the key one.